2015
DOI: 10.1097/bsd.0b013e318286bb14
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Changes in Contralateral Lumbar Foramen in Unilateral Cantilever Transforaminal Lumbar Interbody Fusion Using Kidney-type Intervertebral Spacers

Abstract: Lumbar foraminal dimensions on the side contralateral to spacer insertion increased significantly after c-TLIF, suggesting that c-TLIF enables indirect decompression of the contralateral nerve root. Although increase in posterior disk height was shown to be an important factor to increase contralateral foraminal size, segmental lordosis was a risk factor for a decrease in contralateral foraminal size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 7 publications
0
25
1
3
Order By: Relevance
“…Similar to our hypothesis, Tsuang et al [17] suggested that a unilaterally placed single cage might cause excessive loading on the opposite facet. In contrast to our results, Iwata et al [18] and Anand et al [19] insisted that an anteriorly placed cage may increase lumbar lordosis while the contralateral foramen is narrowed in TLIF surgery. Additionally, Hunt et al [7] suggested that excessive lordosis may cause contralateral radiculopathy.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Similar to our hypothesis, Tsuang et al [17] suggested that a unilaterally placed single cage might cause excessive loading on the opposite facet. In contrast to our results, Iwata et al [18] and Anand et al [19] insisted that an anteriorly placed cage may increase lumbar lordosis while the contralateral foramen is narrowed in TLIF surgery. Additionally, Hunt et al [7] suggested that excessive lordosis may cause contralateral radiculopathy.…”
Section: Discussioncontrasting
confidence: 74%
“…Additionally, Hunt et al [7] suggested that excessive lordosis may cause contralateral radiculopathy. Similarly, Iwata et al [18] also showed that increased lordosis resulted in significantly decreased foraminal dimensions on the side contralateral to spacer insertion. However, they investigated only the anterior-toposterior position of the inserted cages.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7 Cages that lack angulation also influence the vertebral segment lordosis depending on their position on the vertebra body surface (anterior, medial or posterior). [8][9][10] Although Cage positioning in the vertebral segment lordosis is recognizably important 11,12 , there is no consensus on the spacer proper positioning on the body surface. According to Kwon et al 13 , a spacer should be used in the anterior part of the vertebral endplate, achieving greater segment stability and increasing the lordosis of the vertebral segment operated.…”
Section: Introductionmentioning
confidence: 99%
“…However, Faundez et al 8 found that the spacer positioning did not cause a difference in lumbar lordosis, result corroborated by Ould-Slimane et al 10 Cage positioning also influences intervertebral foramen. 9 The contralateral foramen stenosis after performing open TLIF has been related to segmental lordosis hypercorrection. 14,15 The incidence of contralateral radiculopathy, secondary to the reduction of vertebral foramen dimensions after TLIF, is 5.9%.…”
Section: Introductionmentioning
confidence: 99%